Medication Adherence among Patients with Mental Illness Attending Psychiatric OPD & Ward in a Teritiary Hospital at South India (Indian Journal of Public Health Research & Development, 2020)
Background: The purpose of the study was to assess the medication adherence among patients with mentalillness.Methods: The present study adopted descriptive non experimental research design. A total of 70 patientswith mental illness were recruited using a convenience sampling technique. In this study, the data wasobtained through interview technique on demographic variables, medication related variables and medicationadherence scale from samples who were satisfied the inclusion criteria.Results: The study finding revealed that 20 (28.5%) patients had low medication adherence, 27 (38.5%)patients had medium medication adherence and 23 (33%) patients had high medication adherence level.There was a significant association between the level of medication adherence and the residence at the levelof p
Keywords: Medication adherence, mental illness.